Long-Term Intestinal Failure and Home Parenteral Support: A Single Center Experience - Brito,Mariana (2023)
Abstract Introduction: Home parenteral nutrition (HPN) and/or home parenteral hydration (HPH) are the gold-standard treatment for patients with long-term intestinal failure (IF). The authors aimed to assess the impact of HPN/HPH on nutritional status and survival of long-term IF patients, as well as HPN/HPH-related complications. Methods: This was a retrospective study including IF patients under HPN/HPH followed in a single large tertiary Portuguese hospital. The data collected included demographics, underlying conditions, anatomical characteristics, type and duration of parenteral support, IF functional, pathophysiological, and clinical classifications, body mass index (BMI) at the beginning and end of follow-up, complications/hospitalizations, current patient status (deceased, alive with HPN/HPH, and alive without HPN/HPH), and cause of death. Survival after HPN/HPH beginning, until death or August 2021, was recorded in months. Results: Overall 13 patients were included (53.9% female, mean age 63.46 years), and 84.6% of patients presented type III IF and 15.4% type II. Short bowel syndrome caused 76.9% of IF. Nine patients received HPN and 4 HPH. Eight patients (61.5%) were underweight at the beginning of HPN/HPH. At the end of follow-up, 4 patients were alive without HPN/HPH, 4 maintained HPN/HPH, and 5 died. All patients improved their BMI (mean initial BMI 18.9 vs. 23.5 at the end, p < 0.001). Eight patients (61.5%) were hospitalized due to catheter-related complications, mainly infectious (mean hospitalization epi-sodes 2.25, mean hospital stay of 24.5 days). No deaths were related to HPN/HPH. Conclusion: HPN/HPH significantly im-proved IF patients’ BMI. HPN/HPH-related hospitalizations were common, however causing no deaths, reinforcing that HPN/HPH is an adequate and safe therapy for long-term IF patients.